Blade Lift Hydraulic System Troubleshooting on Komatsu D70-LE Bulldozer (Troubleshooting Sistem Hidrolik Blade Lift pada Bulldozer Komatsu D70-LE) - Cipta, Denny Hendra; Harun, Lisa binti; Manglili, Yosua Kombong (Syntax Literate, 2024)
A bulldozer is one type of heavy equipment used for cutting, pushing, and spreading material. It has a blade on the front side whose movement is controlled by a hydraulic system. The movement of the blade, combined with the weight and travel momentum of the bulldozer, creates the mechanical power used in the bulldozer's function.. Problems occurring in the hydraulic system could render the bulldozer useless. In this study, a Komatsu D70-LE bulldozer unit's hydraulic system is experiencing low power and cylinder drift, where the hydraulic cylinder cannot maintain its floating position and tends to return to its full-length rod position, thus causing the blade to drop on itself. This problem is then traced through the troubleshooting method to find the cause and solution to the problem. The cause of the low power problem in the lift cylinder is that the components of the lift cylinder have been worn out and damaged, resulting in a pressure leak in the lift cylinder, which causes the blade to drop by itself (hydraulic drift). The troubling components are the wear ring seal, piston ring seal, o-ring, dust seal, and rod seal. The way to solve the low power problem in the lift cylinder is to replace the lift cylinder seal kit with a new set of wear ring seal, piston ring seal, o-ring, dust seal, and rod seal.